(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
This article explores an actualisation of the Kantian sublime with reference to environmental aesthetics, examining its relevance and transformation in light of the current debate around the ’environmental humanities’. The main thesis of this article is that it is possible to actualise the Kantian sublime in the context of environmental aesthetics, emphasising the counterpurposiveness element of nature. This aspect makes it possible to show a dialectical relationship with nature, overcoming the mere opposition between nature and culture and promoting ethical responsibility. In other words, the sublime can help us recognise the relevance of direct experience of nature and the need for a more respectful and sustainable relationship.